Dust to dust: Evidence for the formation of “primary” hematite dust in banded iron formations via oxidation of iron silicate nanoparticles - Rasmussen, Birger; Muhling, Janet; Suvorova, A.; Krapež, Bryan (Elsevier BV, 2016)
Conventional models for the deposition of banded iron formations (BIFs) envisage the oxidation of upwelled ferrous iron and the precipitation of ferric oxide/hydroxide particles in surface waters that settled to form laterally extensive layers of iron-rich sediment. A fundamental tenet of this model is that fine-grained hematite (so-called dusty hematite) in least-altered BIFs represents the dehydration product of original oxide/hydroxide precipitates. However, this premise has never been proven. We have investigated the origin of the earliest-formed iron oxides in chert in well-preserved BIFs of the 2.63–2.45 billion-year-old Hamersley Group, Australia. We find that laminated chert in BIFs show progressive stages of in situ alteration from gray–green chert, containing iron-silicate nanoparticles, to red chert with abundant hematite dust. Analysis of textures by transmission electron microscopy of samples from the transition zone between gray–green and red chert reveals that dusty hematite formed after partial dissolution of iron-silicate nanoparticles by the precipitation of iron oxides in resulting cavities. These observations suggest that hematite dust is not a relict of an original seawater precipitate but the end-product of post-depositional oxidation. Our observations are consistent with paleomagnetic results from the Hamersley Group, which record two major phases of magnetic remanence carried by hematite that post-date deposition by more than 200 million years. Our results may provide an alternative explanation for the origin of jasper in BIFs deposited before the start of the Great Oxidation Event about 2.4 billion years ago. If correct, it follows that hematite dust is not a reliable proxy for paleoenvironmental conditions or biological processes in early Precambrian seawater. Furthermore, our results suggest that the primary iron precipitate in BIFs was iron-silicate mud that was silicified at or just below the sediment–water interface, a hypothesis that requires neither dissolved oxygen nor photosynthetic life, but was an inorganic, chemical process, reflecting anoxic oceans enriched in iron and silica.